PERANCANGAN APLIKASI PENENTUAN LOKASI PARKIR UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA BERBASIS ANDROID - Andhika Dyansyah (2023)
Effective parking location determination can reduce congestion while traveling to the parking location, improve accessibility, and reduce the time spent looking for parking. The research method used in this research is Waterfall and uses PostgreSQL to design the database and uses PHP, NodeJS, Kotlin, Dbeaver, Netlify and Android Studio to create an android-based parking slot booking application, in order to provide significant benefits in reducing congestion, and improving safe and efficient parking services. Based on the results of the design of the Android-based Parking Slot Booking Information System, the conclusion that can be drawn is that this system provides services for visitors to book parking slots before they arrive at the parking area, so that visitors already get a parking space without having to look for empty parking slots. The suggestions that can be given in the system that has been made are the installation of a parking printer in each parking slot.